2018
DOI: 10.1590/1981-863720180003000073428
|View full text |Cite
|
Sign up to set email alerts
|

Cariology education for undergraduate Brazilian dental students

Abstract: This study sought to provide an overview of current cariology education for undergraduate Brazilian dental students. Data collection was via a Portuguese version of a 12-item questionnaire that was sent to all Brazilian dental schools (n = 219). The response rate was 57.0% (n = 125). Of the schools that returned the questionnaire, 84.8% supported the development of a Brazilian cariology curriculum. The units responsible for teaching cariology were predominantly operative dentistry (49.6%), pediatric dentistry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 15 publications
3
11
0
2
Order By: Relevance
“…43 In Brazil (a Portuguese-speaking country with more than 200 dental schools), the proportion of universities that provided a specific discipline of cariology seemed to be higher than those reported in Europe and other Latin American countries. 44 Apart from these initiatives, there is no regional discussion about the CCC in LACC.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
“…43 In Brazil (a Portuguese-speaking country with more than 200 dental schools), the proportion of universities that provided a specific discipline of cariology seemed to be higher than those reported in Europe and other Latin American countries. 44 Apart from these initiatives, there is no regional discussion about the CCC in LACC.…”
Section: Trends Of and Risk Factors For Dental Caries In Laccs: Summary Of Articles 1 And 2 Of This Consensusmentioning
confidence: 99%
“…168 This was also the case with the 100% consensus being achieved among 15 dental schools in the Caribbean region, 12 in the Dominican Republic, and 1 each in Puerto Rico, Jamaica, and Trinidad and Tobago. 169 In Brazil, information about caries risk is disseminated via Public health and Integrated seminars, risk factors, and determinants 170 and taught in a theoretical manner in most dental schools (94%). 171 In Chile, all universities teach CRA theoretically, 172 with clinical application being taught at only 40% of all dental schools.…”
Section: Discussionmentioning
confidence: 99%
“…Cariology is taught to undergraduate students in public dental schools 34 and caries risk assessment is judged a relevant issue for the Cariology Curriculum, according to 93.6% of the Brazilian dental schools coordinators. 9 On the other hand, a survey with Brazilian public dental schools has demonstrated that in spite of their engagement to teach Cariology, special importance is given to clinical disciplines that disfavor integrated training of dental students. 34 Future studies should address the reasons for not performing CRA among Brazilian dentists as well as the training provided to dental students.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazilian dental schools, CRA was judged a relevant issue for cariology, which is a specific discipline within the curriculum of 32% of Brazilian dental schools or is taught by operative dentistry, pediatric dentistry or public health disciplines. 9 Dentists from a Brazilian community participated in the first study using the Brazilian translated version of the "Assessment of Caries Diagnosis and Caries Treatment" Questionnaire from the National Dental Practice-Based Research Network (National Dental PBRN). The objective of this study was to determine among Brazilian dentists the prevalence of CRA use and factors associated with its use, as well as to quantify dentists' ratings of the importance of specific factors when treatment planning.…”
Section: Introductionmentioning
confidence: 99%